Hygiene and biosecurity practices among traditional poultry farms for the control of zoonotic diseases in rural areas of the Centre-Nord region of Burkina Faso - Ouedraogo, Brice; Ilboudo, Guy S.; Kagambèga, A.; Alders, R.; Ouattara, S.; Knight-Jones, Theodore J.D.; Dione, Michel M. (International Livestock Research Institute, 2024)
Background: In Burkina Faso, traditional poultry farming help communities to earn income and improve their diets. It employs more than 75% of the workforce and is mainly carried out on a small scale. Poultry farmers face many challenges including limited access to health inputs and poor biosecurity measures, posing a risk of transmission of zoonotic diseases through close contact between humans and birds. This study aims to describe the hygiene and biosecurity practices implemented and options for improvement in traditional poultry farms in a rural region characterized by increasing insecurity.